A quantitative approach to weighted Carleson condition - Rivera-Ríos Israel P. (Concrete Operators, 2017)
Quantitative versions of weighted estimates obtained by F. Ruiz and J.L. Torrea [30, 31] for the operator are obtained. As a consequence, some sufficient conditions for the boundedness of Min the two weight setting in the spirit of the results obtained by C. Pérez and E. Rela [26] and very recently by M. Lacey and S. Spencer [17] for the Hardy-Littlewood maximal operator are derived. As a byproduct some new quantitative estimates for the Poisson integral are obtained.